Ангел для Эмили: роман / пер. с англ. И. Швецковой - Деверо Джуд (ОЛМА-пресс, 2003)
Экземпляры: ф.8 (2003) / Инвентарный номер: 46140 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Д 25 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44